All Solutions of the Yang–Baxter-Like Matrix Equation for Nilpotent Matrices of Index Two - Duanmei Zhou; Jiawen Ding (Complexity)
Let A be a nilpotent matrix of index two, and consider the Yang–Baxter-like matrix equation AXA=XAX. We first obtain a system of matrix equations of smaller sizes to find all the solutions of the original matrix equation. When A is a nilpotent matrix with rank 1 and rank 2, we get all solutions of the Yang–Baxter-like matrix equation.